UTILIZATION OF MICROALGAE AS FEED SOURCES IN FISHERIES (Scientific journal of the Fergana State University, 2023)
It has been noted that the use of strains of the genus Botryococcus and Chlorococcum is appropriate for obtaining live feed with a complete nutritional content for the aquaculture industry, including a lower amount of protein (46.2-46.8%) and fat (26.2-26.4%). representatives of the genus Botryococcus were recorded as the genera of microalgae (Chlorococcum and Chlorella genera have high protein content (46.4-48.8%), but fat content (15.6-18.4%) is very low compared to all studied microalgae genera According to the results, representatives of the Botryococcus genus were recorded as microalgae genera that stored a relatively small amount of protein (46.2-46.8%) and fat (26.2-26.4%). Among them, representatives of the Chlorococcum and Chlorella genera stored protein. high (46.4-48.8%), however, oil storage (15.6-18.4%) was determined that it is very low compared to all studied microalgae genera.